The Influence of the Role-Playing Method on the Arabic Speaking Skills of Students at Al-Ghuraba Islamic Boarding School, Dompu. - Ardiansyah, Muhammad; Taufiqurrochman, R; Hasaniyah, Nur (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
The low proficiency in Arabic speaking skills among students at Al-Ghuraba Islamic Boarding School, Dompu, presents a significant challenge in language learning processes. This study aims to analyze the effect of implementing the role-playing method on enhancing students' Arabic speaking skills. A quantitative approach was applied, employing a pre-experimental design of the one-group pretest-posttest type. Data were collected by examining the correlation between pretest and posttest scores following the intervention. The analysis revealed a very high correlation value of 0.86, indicating a significant impact of the role-playing method on speaking skill improvement. These findings suggest that the role-playing method fosters a more active and communicative learning environment, while also boosting students’ confidence in practical Arabic usage. The study highlights the need for broader application of the role-playing method to support the development of Arabic speaking skills within Islamic boarding schools.